Lost diagnoses? A multi-year trajectory of patients with childhood ADHD in the criminal justice system in Switzerland - Wyler, Helen; van Wijnkoop, Moritz; Smith, Alexander; Retz, Wolfgang; Liebrenz, Michael; Buadze, Ana (Frontiers in Psychiatry, 2024)
Background: Attention-deficit/hyperactivity disorder (ADHD) is prevalent amongst offenders, in-creasing risks for aggressive and delinquent behaviours. Since ADHD and its symptoms can persist into adulthood, accurately diagnosing and maintaining diagnoses in offenders is crucial to ensure appropriate treatment and reduce recidivism. Methods: This study employed a retrospective longitudinal design to investigate ADHD amongst adult offenders with a confirmed diagnosis of ADHD during childhood or adolescence at a Swiss forensic outpatient clinic between 2008 and 2021. N = 181 patient files were reviewed, including fo-rensic expert witness assessments and treatment reports. We charted the adulthood trajectory of patients with a confirmed childhood/adolescence ADHD diagnosis, examining the course of their diagnoses. Results: Of 181 patients, evidence indicated that 12 (7%) had an ADHD diagnosis in child-hood/adolescence. In 1 (8%) of these 12 cases, the diagnosis was maintained throughout the obser-vation period. For 4 patients (33%), a diagnosis was given in the first forensic psychiatric expert wit-ness assessment in adulthood but subsequently dropped. In another 4 cases (33%), the diagnosis was dropped in adulthood but later re-assigned, whereas in 3 cases (25%), the diagnosis was discon-tinued throughout the observation period. In 50% of cases with a diagnostic change, the discontinua-tion of an adult ADHD diagnosis coincided with a newly diagnosed personality disorder (or vice ver-sa). Conclusions: Our findings highlighted considerable inconsistencies in the assignment of adult ADHD diagnoses amongst offenders. Whilst ADHD remission in adulthood occurs, the diagnostic variability in our results warrants detailed scrutiny. One possibility is that ADHD has similar fluctua-tions to conditions like depression, as argued elsewhere. Equally, diagnoses may become “lost”, meaning they are not given even when applicable and replaced by other diagnoses. Additionally, residual symptoms may remain but beyond the diagnostic threshold. This is significant because un-treated ADHD can increase re-offending risks and adverse health outcomes.